2014
DOI: 10.1590/s1984-92302014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Elos que libertam: redes de políticas para erradicação do trabalho escravo contemporâneo no Brasil

Abstract: ResumoO objetivo deste artigo foi identificar a dinâmica das relações entre os atores políticos na evolução das políticas públicas para erradicação do trabalho escravo. Para tanto, o estudo contou com pesquisa bibliográfica e de campo, com entrevistas dos seguintes atores: MTE, MPT, OIT, CPT, ONG Repórter Brasil, GPTEC e OAB. Os dados foram analisados pelo método de análise de conteúdo, de viés qualitativo. Os resultados permitiram identificar os atores e suas diferentes estratégias de atuação, a percepção des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
0
4
0
6
Order By: Relevance
“…According to these results, it is observed that, as well as the public policies focused on the theme (Monteiro & Fleury, 2014), companies that adopt anti-slavery practices are more concentrated on supervision and punishment of the chain agents than on prevention actions such as training and caring for the workers. However, repressive actions are necessary but insufficient for the eradication of contemporary slavery (Antero, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to these results, it is observed that, as well as the public policies focused on the theme (Monteiro & Fleury, 2014), companies that adopt anti-slavery practices are more concentrated on supervision and punishment of the chain agents than on prevention actions such as training and caring for the workers. However, repressive actions are necessary but insufficient for the eradication of contemporary slavery (Antero, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation that deserves investigation concerns the political and legal structures responsible for labor inspection in Brazil. The geographic dimension of the country combined with the low number of inspection operations and the lack of knowledge of the worker give scope for the exploitation of contemporary slave labor (Monteiro & Fleury, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse contexto, a política pública para erradicação do trabalho escravo contemporâneo no Brasil é um exemplo de política complexa e que envolve uma cadeia de atores estatais e não estatais para sua execução. As diversas iniciativas governamentais para o combate a esse tipo de exploração evidenciam o envolvimento de uma rede de atores na formulação e implementação da política e a existência de interdependência entre esses atores (Monteiro & Fleury, 2014).…”
Section: Introductionunclassified